(untitled) (Globalization and Business, 2023)
The present article examines the historical aspects of the origin and development of various economic crises existing in the world, which constantly raises an issue of finding ways out of the problem, before scientists-researchers. In this regard, the author reviews the views of the representatives of the classical school of different epochs on the elimination of crises. In addition, the author also analyzes the directions proposed by modern scientists, the most notable of which is the theory of the real economic cycle as an independent direction, which laid the foundation for the systematic study of the economic crisis. Moreover, a conclusion that the slowdown in output growth in market conditions is not due to market inefficiency, but is due to low rates of technological development, and economic cycles are caused by technological shocks is notable. Based on the above assumption, scientists presented an argument, that the market can restore equilibrium without an outside intervention. The cyclical nature of crises followed by economic stimulus is also analyzed.